THE IMPACT OF URBAN AGGLOMERATION ON FISCAL DECENTRALIZATION IN INDONESIA: EVIDENCE FROM NATIONAL PRIORITY METROPOLITAN AREAS - Dian Kania Elizabeth Hasibuan; Andis Destrian Irianto; Mugia Tresna Feira; Elga Yulia Delvira (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Urban agglomeration is a spatial phenomenon that reflects the concentration of population, economic activity, and rapidly developing infrastructure in Indonesia’s metropolitan areas. The government has designated ten National Priority Metropolitan Areas (KMPN) in the National Spatial Plan and the National Medium-Term Development Plan (RPJMN) for 2020-2024 and 2025-2029 as centers of national economic growth; however, this designation has not been accompanied by an empirical study on its impact on fiscal decentralization as mandated by Law No. 33 of 2004. This study aims to analyze the impact of urban agglomeration on the Degree of Fiscal Decentralization (DDF) in 514 regencies and cities across Indonesia in 2022, both directly and through interactions with metropolitan status. Using an explanatory quantitative approach and a census method, urban agglomeration was measured across four dimensions (social, economic, environmental, and infrastructure) and then analyzed using a t-test, simple linear regression, and interaction regression. The results show that the average DDF for metropolitan areas (27.54%) is significantly higher by 18.22 percentage points than that of non-metropolitan areas (9.31%). All four dimensions of agglomeration have a positive and significant effect on DDF, with the infrastructure dimension being the strongest factor (β = 0.163). The interaction model reveals that metropolitan status alone does not necessarily increase DDF; rather, it is highly dependent on the intensity and quality of agglomeration (interaction β = 0.1795; p < 0.001). These findings recommend intensifying infrastructure development, fostering agglomeration-based economic clusters, strengthening cross-regional metropolitan governance, and establishing a national agglomeration monitoring system to enhance local fiscal autonomy.